2005
DOI: 10.1109/tasc.2005.849173
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of AC Loss Characteristics of High Temperature Superconducting Coil

Abstract: This paper reports an analytical study on AC loss characteristics of a high temperature superconducting coil wound with a Bi2223/Ag tape. The electromagnetic AC loss in the high temperature superconducting coil made by stacking pancake coils wound with the Bi2223/Ag tape was numerically calculated by using the measured DC data of the HTS tape. The calculated AC loss was compared with measured AC losses in Bi2223 HTS coils obtained in a previous study. It had been found that the measured AC losses in the coils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, in this study, we focused on glucose uptake in adipocytes. Previous studies have indicated that the AMPK activator, AICAR, accelerates GLUT4 translocation in adipocytes [15]. Thus, we hypothesized that LFV may promote AMPK-mediated GLUT4 translocation in adipocytes.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 91%
“…Therefore, in this study, we focused on glucose uptake in adipocytes. Previous studies have indicated that the AMPK activator, AICAR, accelerates GLUT4 translocation in adipocytes [15]. Thus, we hypothesized that LFV may promote AMPK-mediated GLUT4 translocation in adipocytes.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 91%
“…The total AC loss in the HTS coil is approximately estimated by the summation of the total AC loss in the HTS tape over the coil cross section [4]. The total AC loss in the HTS coil is approximately estimated by (1) where is the center position of the superconductor area of the HTS tape in the coil cross section, is the total AC loss per unit length in the HTS tape at , is the magnetic field of -component at which is perpendicular to the tape surface and is the peak value of AC coil current.…”
Section: A Ac Loss Analysismentioning
confidence: 99%
“…In our previous study [1]- [5], we have proposed a method to approximately estimate the AC loss in the HTS coil by the summation of the total AC loss in the HTS tape over the coil cross section. It has been shown that the experimental AC loss characteristics of the HTS coils wound by the Bi2223/Ag [4]. From these previous works [3]- [5], we have obtained an idea that the AC loss in the HTS coil can be minimized by optimizing the winding cross section.…”
Section: Introductionmentioning
confidence: 99%